MICRO, SMALL, MEDIUM ENTERPRISES (MSMEs) DEVELOPMENT THROUGH INSTAGRAM DIGITAL CONTENT, DESCRIPTIVE QUALITATIVE ANALYSIS @Bagja.id - Zaelani, Pupi Indriati; Yulianti, Alin; Munastha, Ketut Abimanyu; Lestari, Nina; Muzakki, Ahmad (TOPLAMA, 2025)
Social media is now not only a platform for sharing photos and videos but has become a channel for MSMEs to promote their products. This research will discuss how the @bagja.id account uses visual and narrative content on Instagram to build a strong brand image and increase the visibility of the MSMEs it represents. This research method uses a descriptive qualitative method in which a social phenomenon will be analyzed and interpreted and then connected with relevant theories. The results of this research show that the management of an MSME account must be managed well by paying attention to the use of hashtags, copywriting, and building interaction with followers. The important thing to pay attention to is how the process of building interaction with followers in account management is very important because this can build brand awareness. Based on an analysis of the @Bagja.id account, it can be concluded that they have succeeded in adopting a soft-selling marketing strategy with a focus on visual content such as photos, videos, and reels.  Apart from that, managing content and information in the account is very important to create a relationship between the account and followers which will later create brand awareness.